„Notre Pologne” (1930–1939) jako przykład kształtowania wiedzy o Polsce wśród francuskiej młodzieży - Seroka, Katarzyna (Biuletyn Historii Wychowania, 2019)
In 1919 Rosa Bailly, a French enthusiast of Poland, established the Les Amis de la Pologne, a socio-cultural society propagating knowledge about Poland and its culture. This activity was supplemented by a publishing business. 1930 marked the beginning of publishing ‘Notre Pologne’, a monthly magazine for teenagers. The aim of the magazine was to attract young people to the association. The article presents the history and ideology of the periodical, its impact and the way of educating about Poland and its cultural heritage.